A broad‐based study on hyphenating new ionization technologies with MS/MS for PTMs and tissue characterization. Issue 11 (15th June 2016) - Marshall, Darrell D.; Inutan, Ellen D.; Wang, Beixi; Liu, Chih‐Wei; Thawoos, Shameemah; Wager‐Miller, James; Mackie, Ken; Trimpin, Sarah
Abstract : Matrix‐assisted ionization (MAI) is a newly discovered method for converting compounds from the solid phase to gas‐phase ions having charge states similar to electrospray ionization (ESI), but without the need for high‐energy sources such as lasers or high voltage. Laserspray ionization (LSI) is a subset of MAI that uses a laser to provide high spatial resolution analyses, but the laser is not directly involved in the ionization process. These methods produce multiply‐charged analyte ions that are useful for characterizing compounds directly from surfaces using advanced characterization technologies. Because the multiply‐charged ions originate from charged matrix clusters, efficient desolvation of the matrix is a prerequisite. Here, we report on the utility of collision‐induced dissociation (CID) and electron transfer dissociation (ETD) coupled to mass spectrometry using several MAI and LSI matrices for peptide and protein characterization employing mass spectrometers from two manufacturers. The information obtained is similar to that using ESI for most analyses and superior to matrix‐assisted laser desorption/ionization (MALDI) as is shown for intact proteins and protein digests directly from mouse brain tissue sections. The ionization processes are soft so that posttranslational modification (e.g. phosphorylation) sites are readily determined. Instances where ETD or CID in conjunction with MAI failed are attributed to lack of desolvation of charged matrix:analyte particles.